Gastric Cardia Adenocarcinoma with Metastasis to the Scalp: A Case Report - Menghani, Sanjay V (Cureus, 2020)
Cutaneous metastasis is a rare manifestation of advanced gastrointestinal (GI) cancers. Gastric adenocarcinoma rarely presents with cutaneous metastasis, as cutaneous manifestations occur in less than 1% of upper GI tract malignancies. Here, we present the case of a patient with advanced gastric cardia adenocarcinoma with metastasis to the right occipital region of the scalp. Following shave biopsy, the immunohistochemistry (IHC) and molecular profile of the scalp lesion were analyzed, both of which confirmed metastasis and guided the treatment approach. The lesion demonstrated programmed death ligand-1 (PD-L1), an immune checkpoint protein, positivity by IHC, which led to the recommendation for treatment with immunotherapy as per the National Comprehensive Cancer Network (NCCN) guidelines. Clinicians should conduct dermatologic examinations in patients with a history of gastric cancer or who are currently undergoing chemotherapy for gastric cancer in order to monitor for disease progression or metastatic lesions. The aim of this report is to increase awareness of scalp metastasis as an indicator of advanced internal visceral carcinoma for earlier diagnosis and improved management of the condition.